Home office and health outcomes of adults in southern Brazil - Meller, Fernanda Oliveira; Dumith, Samuel de Carvalho; Quadra, Micaela Rabelo; Eugenio, Fernanda Daminelli; Maciel, Elisabete Borges; Mendes, João Vitor Santana; Petry, Sofia Garbin; Patricio, Vinicius Alves; Schäfer, Antônio Augusto (ABCS Health Sciences, 2024)
Introduction: During the COVID-19 pandemic, the home office was of paramount importance for the continuity of work functions and home economic maintenance. However, this practice can influence the population’s lives. Objective: To assess the relationship between working from home during the COVID-19 pandemic and health outcomes in two cities in Southern Brazil. Methods: This is a cross-sectional, population-based study, conducted between 2020 and 2021, in two cities from Southern Brazil: Criciúma (Santa Catarina) and Rio Grande (Rio Grande do Sul). Individuals aged 18 years or older, residing in the urban area of the cities, were eligible for the study, and the sampling process was conducted in two stages, with the random selection of census tracts and households. The exposure variable was the home office during the pandemic. The outcomes studied were sleep, physical activity, body weight, food consumption, smoking, and alcohol intake. Results: 2,170 individuals were studied, and the prevalence of home office was 7.7%. Higher prevalence of home office was found in individuals aged up to 49 years (p<0.001), white skin color (p=0.036), university education (p<0.001) and richer (p<0.001). In the adjusted analysis, the home office was associated with more likely to increase the practice of physical activity (PR=1.95; 95%CI 1.06-3.58) and increasing the consumption of healthy foods (PR=2.37; 95%CI 1.58-3.54), during the COVID-19 pandemic. Conclusion: These results demonstrate that home office during the COVID-19 pandemic had positive repercussions on some health outcomes in adults from Southern Brazil.